Obstructive Sleep Apnea Monocytes Exhibit High Levels of Vascular Endothelial Growth Factor Secretion, Augmenting Tumor Progression. (28th May 2018) - Cubillos-Zapata, Carolina; Hernández-Jiménez, Enrique; Avendaño-Ortiz, José; Toledano, Victor; Varela-Serrano, Anibal; Fernández-Navarro, Isabel; Casitas, Raquel; Carpio, Carlos; Aguirre, Luis A.; García-Río, Francisco; López-Collazo, Eduardo
Abstract : Obstructive sleep apnea (OSA) is a syndrome characterized by repeated pauses in breathing induced by a partial or complete collapse of the upper airways during sleep. Intermittent hypoxia (IH), a hallmark characteristic of OSA, has been proposed to be a major determinant of cancer development, and patients with OSA are at a higher risk of tumors. Both OSA and healthy monocytes have been found to show enhanced HIF1 α expression under IH. Moreover, these cells under IH polarize toward a tumor-promoting phenotype in a HIF1 α -dependent manner and influence tumor growth via vascular endothelial growth factor (VEGF). Monocytes from patients with OSA increased the tumor-induced microenvironment and exhibited an impaired cytotoxicity in a 3D tumor in vitro model as a result of the increased HIF1 α secretion. Adequate oxygen restoration both in vivo (under continuous positive airway pressure treatment, CPAP) and in vitro leads the monocytes to revert the tumor-promoting phenotype, demonstrating the plasticity of the innate immune system and the oxygen recovery relevance in this context.